Effect of Different Methods of Biofertilizer Application in Tomato Seed Production - SATESH KUMAR,; S.K. SHARMA, (Seed Research, 2026)
An investigation using four biofertilizers namely Azotobacter, Azospirillium, Pseudomonas and Vesicular arbuscular mycorrhiza (VAM) was undertaken during summer season of 2002 and repeated in 2003, to study their role on various aspects of tomato seed production. Application of these biofertilizers was done with three methods ie nursery soil treatment, seedling treatment and field soil treatment, tried individually and in combinations thereof. Basal application of FYM (25t/ha) was given to all the plots except control where only recommended dose of NPK (100,75 and 55 kg/ha) was applied. The study revealed that Azotobacter when applied to nursery, seedling and field soil, resulted in maximum values with respect to number of fruits per plant(19.23), fruit yield per plant(1109g), per hectare (356.9q) 1000 seed weight (3.63g), seed yield per plant (4.58g), per hectare (152.70kg) along with C:B ratio (1:1.45). However, the results with respect to germination percentage of seeds remained non-significant.